Efficiency of application of the complex based on pseudomonas fluorescens bacteria on potato plantations in the Western Forest Steppe of Ukraine - GavryluckА.; Solomiychuk, M.; Rozhok, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To form effective complexes based upon bacterium Pseudomonas fluorenscens in combination with stimulation growth preparations and microelements with their efficiency study on potato plantations. Methods. The researches conducted during 2021—2022 in breeding- seeding rotation on the base Ukrainian Research Plant Quarantine Station of Institute of Plant Protection of NAAS. The experiment conducted on variety Slovyanka. The preparations efficiency determined in different rates against fungi diseases. Records conducted as per generally approved techniques with experimental methods in plant pathology and plant protection. Results. The efficiency of complex based upon Pseudomonas fluorescens АР-33 with stimulating matter nature and chelated microelementson potato plantations in growing period. The yield increased in 1.1—1.5 times during chelate 1 adding to preparation based upon bacterium Pseudomonas fluоrescens, and it increased in 1.3—1.6 times during chelate 2 addition. All biocomplexes combinations showed the preparation efficiency against Alternaria blight in scope 41.5—66.8%, but for late blight it had the following indexes 65.6—85.2. Conclusions. Combinations with chelates № 2 (Fe + Mn + Zn + Mo + Co + B) provided best growing results and yield. The combination Pseudomonas fluоrescens + xymedon + accinic acid + DMAE2ml/l + DМSО2 ml/l chelate (3.6%) showed the best result against potato Alternaria blight. It’s efficiency consisted of 66.8%.The combination Pseudomonas fluоrescens + xymedon + accinic acid + DMAE2ml/l + DМSО2 ml/l chelate(3.6%) showed 85.2% against late blight. It was the best index.